Kurikulum PAI Berbasis Pesantren di MI Ya Bakii 01 Kesugihan Cilacap - Tsabit Itmamurizal; Agus Sutiyono; Fahrurrozi, Fahrurrozi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The aim of this research is to reveal the Islamic boarding school-based PAI curriculum, including the objectives of the PAI curriculum, PAI curriculum content, learning experiences and orientation competencies for Islamic boarding school-based students. The place of this research is MI Ya BAKII 01 Kesugihan Cilacap. This research uses qualitative research with a case study approach, using triangulation of techniques, sources and informants. The data that the author obtained was through interviews, observation and documentation. Then each data is analyzed using an interactive cycle with components of data reduction, data presentation and conclusion drawing. The results of the research show that there are general objectives of the PAI curriculum, namely the formation of student character, and specific objectives, namely to support madrasa subjects. The content of the Islamic boarding school-based PAI curriculum is linear activities with the Al Ihya Ulumaddin Kesugihan Islamic boarding school as the Islamic boarding school that houses the Ya BAKII foundation, such as; Tahfidzul Qur'an, Muroja'ah, learning lectures, making prayers (sholawatan) and learning the Qur'an and prayer. The implementation of the Islamic boarding school-based PAI curriculum at MI Ya Bakii 01 is carried out in the classroom and outside the classroom, every day according to a predetermined schedule. The Islamic boarding school-based PAI learning orientation is carried out by prioritizing discipline and morals in the madrasah and outside the madrasah.